FACTORS OF STUNTING IN TODDLERS: A LITERATURE REVIEW - Filiyanti Halim; Ermiati Ermiati; Eka Afrima Sari (Universitas Padjadjaran, 2021)
Stunting in toddlers is one of the health problems that has not been resolved globally, also in Indonesia. Stunting can be prevented by early detection based on the risk factors for the disease. The literature review aims to examine those articles and find out every risk factor for stunting in toddlers. This literature study used a scoping review method by searching through several search engines such as Google Scholar, ProQuest, PubMed, and EBSCO. After sorting the articles, there are 21 articles used in this literature study. The results of this literature study showed twenty-one risk factors for stunting in toddlers, such as exclusive breastfeeding and the initiation of early breastfeeding. A history of low birth weight, immunization, the number of family members, insufficient nutritional needs (energy, iron, protein, calcium, and zinc), colostrum, breastfeeds (age of administration, type, and frequency). The practice of washing hands, mothers' occupation, mothers knowledge, low family income, history of infectious disease, sanitation and cleanliness of the environment, parents' height, especially mothers, lack vitamin C and vitamin D also as risk factors for stunting. To conclude, stunting in toddlers was influenced by various factors which are child factors, parents, socio-economic, and environmental factors. Therefore, it is essential to consider all the factors to develop stunting early detection tools for toddlers ang health education materials.